Exercise capacity of vegan, lacto-ovo-vegetarian and omnivorous recreational runners - Josefine Nebl; Sven Haufe; Julian Eigendorf; Paulina Wasserfurth; Uwe Tegtbur; Andreas Hahn (Taylor & Francis Group, 2019)
Background In search of the right nutrition for the athlete, numerous nutritional strategies and diets were discussed over time. However, the influence of plant-based diets, especially veganism, on exercise capacity has not been clarified. Methods We conducted a cross-sectional study to compare the exercise capacity of vegan (VEG, n = 24), lacto-ovo-vegetarian (LOV, n = 26) and omnivorous (OMN, n = 26) recreational runners. To determine maximal exercise capacity, participants performed an incremental exercise test on a bicycle ergometer until voluntary exhaustion. During the test capillary blood samples were taken at several time points for the measurement of arterial lactate [lac] and glucose [glc] concentrations. To determine nutrient intake, a 24 h dietary recall was conducted. Results The groups showed comparable training habits in terms of training frequency (mean 3.08 ± 0.90 time/wk., p = 0.735), time (mean 2.93 ± 1.34 h/wk., p = 0.079) and running distance (mean 29.5 ± 14.3 km/wk., p = 0.054). Moreover, similar maximum power output (PmaxBW) was observed in all three groups (OMN: 4.15 ± 0.48 W/kg, LOV: 4.20 ± 0.47 W/kg, VEG: 4.16 ± 0.55 W/kg; p = 0.917) and no differences regarding [lac] throughout the exercise test and maximum lactate could be observed between the groups (OMN: 11.3 ± 2.19 mmol/l, LOV: 11.0 ± 2.59 mmol/l, VEG: 11.9 ± 1.98 mmol/l; p = 0.648). Conclusion The data indicate that each examined diet has neither advantages nor disadvantages with regard to exercise capacity. These results suggest that a vegan diet can be a suitable alternative for ambitious recreational runners. Trial registration German Clinical Trials Register (DRKS00012377). Registered on 28 April 2017